Tobacco and menthol flavored nicotine-free electronic cigarettes induced inflammation and dysregulated repair in lung fibroblast and epithelium - Qixin Wang; Joseph H Lucas; Cortney Pang; Ruogang Zhao; Irfan Rahman (Respiratory Research, 2024)
Abstract Background Electronic cigarette (e-cig) vaping has increased in the past decade in the US, and e-cig use is misleadingly marketed as a safe cessation for quitting smoking. The main constituents in e-liquid are humectants, such as propylene glycol (PG) and vegetable glycerine (VG), but different flavoring chemicals are also used. However, the toxicology profile of flavored e-cigs in the pulmonary tract is lacking. We hypothesized that menthol and tobacco-flavored e-cig (nicotine-free) exposure results in inflammatory responses and dysregulated repair in lung fibroblast and epithelium. Method We exposed lung fibroblast (HFL-1) and epithelium (BEAS-2B) to Air, PG/VG, menthol flavored, or tobacco-flavored e-cig, and determined the cytotoxicity, inflammation, and wound healing ability in 2D cells and 3D microtissue chip models. Results After exposure, HFL-1 showed decreased cell number with increased IL-8 levels in the tobacco flavor group compared to air. BEAS-2B also showed increased IL-8 secretion after PG/VG and tobacco flavor exposure, while menthol flavor exposure showed no change. Both menthol and tobacco-flavored e-cig exposure showed decreased protein abundance of type 1 collagen α 1 (COL1A1), α-smooth-muscle actin (αSMA), and fibronectin as well as decreased gene expression level of αSMA (Acta2) in HFL-1. After tobacco flavor e-cig exposure, HFL-1 mediated wound healing and tissue contractility were inhibited. Furthermore, BEAS-2B exposed to menthol flavor showed significantly decreased tight junction gene expressions, such as CDH1, OCLN, and TJP1. Conclusion Overall, tobacco-flavored e-cig exposure induces inflammation in both epithelium and fibroblasts, and tobacco-flavored e-cig inhibits wound healing ability in fibroblasts.